Information technology an introduction for today's digital world - Fox, Richard 1964 (CRC Press, 2020)
"This revised edition has more breadth and depth of coverage than the first edition. Information Technology: An Introduction for Today's Digital World introduces undergraduate students to a wide variety of concepts they will encounter throughout their IT studies and careers. It offers a far more detailed examination of the computer and the IT field than computer literacy texts, focusing on concepts essential to all IT professionals-from system administration to scripting to computer organization. Four chapters are dedicated to the Windows and Linux operating systems so that students can gain hands-on experience with operating systems that they will deal with"-- c Provided by publisher